Pengaruh Kalsium Klorida (CaCl2) dan Lama Penyimpanan terhadap Kadar Vitamin C Anggur (Vitisvinifera) - Anny Thuraidah; haitami haitami; Akhmad Dairobi (Medical Laboratory Technology Journal, 2015)
Vitisvinifera is one of the perishable fruit and not durable when stored at room temperature. To maintain the levels of vitamin C wine then used treatment using calcium chloride (CaCl2). This study aims to determine the effect of treatment Calcium chloride (CaCl2) and duration of storage of the vitamin C content of Vitisvinifera This type of research uses experimental methods actual (true experiment) in the form of draft posttest only control group design. Wine and CaCl2 research materials. Data were obtained by performing assays using titration iodometry vitamin C in grapes. Results of statistical analysis to test multiple linear regression R2 values ​​obtained showed no effect of treatment 0.578 Calcium chloride (CaCl2) and storage time for blood levels of vitamin C Vitisvinifera. From Duncan statistical test obtained significant value for all subsets of the 2 treatment groups of more than 0.05, the most optimal levels of vitamin C in maintaining the Vitisvinifera is a CaCl2 concentration of 0.05 M for 4 days of storage. Therefore, this study suggested as alternative preservation for merchants and producers / grape growers in order to maintain the vitamin C content of wine so as to improve the quality and the quality of the fruit.